Programa Senac de Gratuidade: um estudo do percurso de formação do aluno egresso - Rocha, Darlan Oliveira (2021)
The Free Agreement is a commitment made by the Confederation of Commerce (CNC) with the Federal Government to expand the use of resources from its National Apprenticeship Service (National Commercial Apprenticeship Service - Senac) and Social Service (Social Service of Commerce) - Sesc) in the free offer of professional education courses. Given the transfer of financial resources by the Union to carry out the program, it is necessary to analyze it in order to understand it due to its relevance as a public policy of professional training, as well as the benefits and / or losses provided to students fellows (alumni). To this end, we consider the offers of free places at the Itaquera educational unit, part of the Senac São Paulo unit network, located in the neighborhood of the same name, on the east side of São Paulo, applying qualitative and quantitative research, followed by analysis documentary, the study of data and collected narratives, with the general objective of understanding the professional training path of the graduates (scholarship students) of the program called Senac de Gratuidade (PSG), having as specific objectives: i) the analysis of public policy from the graduate's current professional situation; ii) the analysis of public policy from the experience as a beneficiary (scholarship student); iii) the understanding of the narratives of the trajectory of a scholarship student to egress, as a professional in the job market. Regarding the foundations of this research we have in the capital and labor relation of Marx (1818 - 1833), in the class struggles in Gramsci (1891 - 1937) and in the emancipatory dialogic pedagogy of the oppressed (continuous process of education and change) by Paulo Freire (1921 - 1997), the founding bases, which allows us to affirm at last, the formation path of the egressed student, characterized by a professional education beyond the technical, of an emancipatory character, and why not say, subversive, that when stimulating the student to the exercise of thought, promotes reflection, self-criticism and criticism, having in practice (from a positive perspective) the driving force for change; first, in becoming aware of his condition as a subject; second, in becoming aware of his condition as a subject in the world; and third, in taking his condition as a subject in the world as an agent of change.